2022
DOI: 10.15251/djnb.2022.173.979
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial potential of silver nanoparticles synthesized using tri-sodium citrate via controlled exploitation of temperature

Abstract: In present work, synthesis of silver nanoparticles (AgNPs) has been reported by utilizing tri-sodium citrate (TSC) as reducing and stabilizing agent. The effect of temperature and molar ratio of silver salt (AgNO3) and TSC has been studied on the size and morphology of nanoparticles. The synthesized AgNPs were characterized by Powder X-ray Diffraction (XRD), UV-Visible spectroscopy (UV-Vis.), Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray spectroscopy (EDS). Biological evaluation of the optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Through XRD diffractogram, data obtained can be used to determine the crystal size through the value of full width at half maximum (FWHM). The crystal size is calculated using the Scherer Equation as in Equation (2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through XRD diffractogram, data obtained can be used to determine the crystal size through the value of full width at half maximum (FWHM). The crystal size is calculated using the Scherer Equation as in Equation (2).…”
Section: Resultsmentioning
confidence: 99%
“…According to Tran et al, silver nanoparticles (AgNPs) have higher electrical and thermal conductivity than other metals [1]. The most widespread application of AgNPs is antibacterial [2] and antiviral in light of the COVID-19 pandemic [3]. AgNPs are also used in the textile industry in membrane filtration of water purifications [4], sensors [5], and catalysts [6].…”
Section: Introductionmentioning
confidence: 99%
“…Saxena and Ayushi [29] have reported the fungicidal characteristics of AgNPs synthesized even from the plant pathogenic fugal strain S. sclerotiorum MTCC 8785 against the T. harzianum strain. Findings of Zamana et al [30] demonstrated that AgNPs were more effective antibacterials than conventional rifampicin as they obtained comparatively modest inhibition zones against gram-positive and gram-negative bacteria than those achieved by conventional rifampicin. Revathi et al [31] and Arsene et al [32] found that papaya's extracts are very effective reducing agents for the biogenic production of AgNPs; later, they further explained that AgNPs that are synthesized biologically using seed and root extract exhibit notable antibacterial as well as antibiofilm capabilities [32].…”
Section: Discussionmentioning
confidence: 99%
“…Chemical reduction is the most frequently applied method for synthesizing silver nanoparticles as a stable colloidal dispersion in water or organic solvents [18]. In this nanosilver synthesis, sodium citrate is used as a reducing agent and stabilizer [19]. Research [20] said that synthesizing nanosilver using sodium citrate as a reducing agent and stabilizer will produce nanosilver particles with a spherical shape with particle sizes ranging from 30-60 nm.…”
Section: Introductionmentioning
confidence: 99%